Determination of polar aromatic amines using newly synthesized sol-gel titanium (IV) butoxide cyanopropyltriethoxysilane as solid phase extraction sorbent - Miskam, Mazidatulakmam Akmam; Abu Bakar, Nor Kartini; Mohamad, Sharifah (Elsevier BV, 2014)
A solid phase extraction (SPE) method has been developed using a newly synthesized titanium (IV) butoxide-cyanopropyltriethoxysilane (Ti-CNPrTEOS) sorbent for polar selective extraction of aromatic amines in river water sample. The effect of different parameters on the extraction recovery was studied using the SPE method. The applicability of the sorbents for the extraction of polar aromatic amines by the SPE was extensively studied and evaluated as a function of pH, conditioning solvent, sample loading volume, elution solvent and elution solvent volume. The optimum experimental conditions were sample at pH 7, dichloromethane as conditioning solvent, 10 mL sample loading volume and 5 mL of acetonitrile as the eluting solvent. Under the optimum conditions, the limit of detection (LOD) and limit of quantification (LOQ) for solid phase extraction using Ti-CNPrTEOS SPE sorbent (0.01-0.2; 0.03-0.61 μgL-1) were lower compared with those achieved using Si-CN SPE sorbent (0.25-1.50; 1.96-3.59 μgL-1) and C18 SPE sorbent (0.37-0.98; 1.87-2.87 μgL -1) with higher selectivity towards the extraction of polar aromatic amines. The optimized procedure was successfully applied for the solid phase extraction method of selected aromatic amines in river water, waste water and tap water samples prior to the gas chromatography-flame ionization detector separation.